Hydraulic modelling : an introduction : principles, methods and applications - Novák, Pavel, 1918- (Spon, 2010)
Presents a synthesis between classical physical models and the extensive range of constantly evolving computational techniques. This title shows how to pick the right model and to appreciate its strengths and limitations.